2013
DOI: 10.11648/j.ijmsa.20130202.15
|View full text |Cite
|
Sign up to set email alerts
|

Love Wave Propagation in Electro-Magneto Non-Homogeneous Elastic Media

Abstract: Abstract:A mathematical approach is taken to investigate Love wave propagation in non-homogeneous electromagneto-elastic media. The elastic media is assumed to be initially unstressed and at rest. In this study, it is assumed that mass density '

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…In 2014, Zhang [ 24 ] studied the Rayleigh wave’s characteristics in a magneto-electro-elastic half-space with initial stress by using the quasistatic approximation and linearity assumption. Through assuming the material properties are space dependent, the Love wave propagation in non-homogeneous electro-magneto-elastic half-space was explored by employing the mathematical approach [ 25 ]. Later on, it was found that in different cross sections the surface wave velocity can have significant change due to the rotary symmetry of crystal [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, Zhang [ 24 ] studied the Rayleigh wave’s characteristics in a magneto-electro-elastic half-space with initial stress by using the quasistatic approximation and linearity assumption. Through assuming the material properties are space dependent, the Love wave propagation in non-homogeneous electro-magneto-elastic half-space was explored by employing the mathematical approach [ 25 ]. Later on, it was found that in different cross sections the surface wave velocity can have significant change due to the rotary symmetry of crystal [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a vast majority of articles analyzing properties of Love surface waves in geophysics, sensors, and layered composite materials, Love wave waveguides were considered to be entirely lossless (Kakar and Kakar, 2012; Kundu et al, 2014; Singh, 2010). However, real Love wave waveguides have to be necessarily lossy because of the inherent viscoelastic properties of the constituent materials, and an extra loading with a viscous liquid, in the case of sensors.…”
Section: Introductionmentioning
confidence: 99%
“…The active use of composite structures based on electroelastic and magnetoelastic materials when creating modern devices based on coupled physical and mechanical fields requires a detailed study of the physical processes of composite structures. The analytical solution for dispersion of love waves for electromagnetically short and open case was obtained in [1]. Dynamic solution for the propagation of harmonic waves in imhomogeneous magneto-electro-elastic medium made of BaTiO3 and CoFe2O4 is presented in [2].…”
Section: Introductionmentioning
confidence: 99%